Exploring the Role of Women in Entrepreneurship: An Analysis of the Motivations and Challenges of Female Entrepreneurs in Greater Malang - Kharisma, Iffah Nur; Susilowati, Christin (Universitas Airlangga, 2025)
This study uses a qualitative phenomenological approach to explore the lived experiences of female entrepreneurs in Greater Malang, focusing on their motivations for starting a business and the challenges they face in sustaining it. Data were collected through in-depth interviews with women business owners and analysed through three stages: first-order concepts, second-order themes, and aggregate dimensions. The results reveal five main motivational dimensions: altruism, cultural heritage, economic orientation, pleasure, and self-empowerment. On the other hand, challenges are classified into internal and external categories, including work-life balance, lack of technical skills, health concerns, limited funding, role conflict, and lack of public recognition. This research highlights the unique lived experiences of women entrepreneurs, particularly the way they navigate social expectations and resource limitations while pursuing business sustainability. The findings contribute to the broader understanding of women’s entrepreneurship and provide insights for supportive policy development.